Parents' views about healthcare professionals having real‐time remote access to their young child's diabetes data: Qualitative study - Kimbell, Barbara; Rankin, David; Hart, Ruth I.; Allen, Janet M.; Boughton, Charlotte K.; Campbell, Fiona; Fröhlich‐Reiterer, Elke; Hofer, Sabine E.; Kapellen, Thomas M.; Rami‐Merhar, Birgit; Schierloh, Ulrike; Thankamony, Ajay; et al. (Pediatric diabetes, 2022)
Objectives We explored parents' views about healthcare professionals having remote access to their young child's insulin and glucose data during a clinical trial to inform use of data sharing in routine pediatric diabetes care. Research Design and Methods Interviews with 33 parents of 30 children (aged 1–7 years) with type 1 diabetes participating in a randomized trial (KidsAP02) comparing hybrid closed‐loop system use with sensor‐augmented pump therapy. Data were analyzed using a qualitative descriptive approach. Results Parents reported multiple benefits to healthcare professionals being able to remotely access their child's glucose and insulin data during the trial, despite some initial concerns regarding the insights offered into everyday family life. Key benefits included: less work uploading/sharing data; improved consultations; and, better clinical input and support from healthcare professionals between consultations. Parents noted how healthcare professionals' real‐time data access facilitated remote delivery of consultations during the COVID‐19 pandemic, and how these were more suitable for young children than face‐to‐face appointments. Parents endorsed use of real‐time data sharing in routine clinical care, subject to caveats regarding data access, security, and privacy. They also proposed that, if data sharing were used, consultations for closed‐loop system users in routine clinical care could be replaced with needs‐driven, ad‐hoc contact. Conclusions Real‐time data sharing can offer clinical, logistical, and quality‐of‐life benefits and enhance opportunities for remote consultations, which may be more appropriate for young children. Wider rollout would require consideration of ethical and cybersecurity issues and, given the heightened intrusion on families' privacy, a non‐judgmental, collaborative approach by healthcare professionals.